Analysis of socio-demographic status and clinical manifestations among SARS-CoV-2 patients in ethnic tribal population of Mizoram, Northeast India: A retrospective study from single-tertiary COVID-19 care centre - P.C. Lalrohlua; Gracy Laldinmawii; John Zohmingthanga; Jane Ralte; Lalengkimi Ralte; John Zothanzama; Nachimuthu.Senthil Kumar; Swagnik Roy (Elsevier, 2024)
Background: The study assesses the impact of socio-demographic factors, including food habits and lifestyle factors, with their clinical outcome due to SARS-CoV-2 in a small tribal state in Northeast India. Methods: Clinical and demographic data from 896 patients with elevated levels of cytokine were collected, retrospectively. The data was analyzed using IBM SPSSv.26 statistics to assess the correlation between the variables and the impact on patient's clinical outcomes. Results: The data consisted of 48.8% male and 51.2% female patients and the mean age was 30.73 years. The symptoms recorded during the hospital stay were anosmia followed by fever, cough, dysgeusia, hypertension, diabetes, diarrhoea, obesity, and shortness of breath. Comorbidities such as malnourishment, kidney diseases, cancers, and immune-compromised were found among them. Moreover, 67% were at risk of respiratory infection and the mean duration of hospital stay was 12-13 days. There was moderate consumption across all food types except for vegetables and smoked food and most patients didn't consume alcohol or smoke. A significant positive association was found both for respiratory infection (p = 0.001) and bad liver function (p = 0.045) with the duration of hospital stay. Individuals who do not consume gutkha (a blended areca nut with tobacco) tend to have lower ct-values (p = 0.011). Alcohol consumption was also significant with shortness of breath (p = 0.009), while smoking was significantly associated with anosmia (p = 0.044) and chest pain (p = 0.002). Conclusions: The demographic and health conditions were mostly not associated with the clinical outcome which could indicate that these practices might instead increase the recovery rate and in turn lower the death rates within the population.